Comparative outcomes of total hip and knee arthroplasty: a prospective cohort study. Issue 1045 (21st July 2012) - Hamilton, David; Henderson, G Robin; Gaston, Paul; MacDonald, Deborah; Howie, Colin; Simpson, A Hamish R W
Abstract : Purpose: The comparative outcome of primary hip and knee arthroplasty is not well understood. This study aimed to investigate the outcome and satisfaction of these procedures and determine predictive models for 1 year patient outcome with a view to informing surgical management and patient expectations. Study design: Prospective cohort study of all primary hip and knee arthroplasty procedures performed at the Royal Infirmary of Edinburgh between January 2006 and November 2008. General health (SF-12) and joint specific function (Oxford Score) was assessed pre-operatively and at 6 and 12 months post-operatively. Patient satisfaction was assessed at 12 months. Results: 1410 total hip arthroplasty (THA) and 1244 total knee arthroplasty (TKA) procedures were assessed. Oxford Score improved by 4.9 points more in THA patients than in TKA patients. SF-12 physical scores were on average 2.7 points greater in the THA patients at one year. Satisfaction was also greater (91%) following THA compared with TKA (81%). Regression modelling was not able to predict individual patient outcome; however, mean pre-operative Oxford Scores were found to be strong predictors of mean post-operative Oxford Scores for each procedure. Age, gender and pre-operative general health scores did not influence these models. Conclusions: Both THA and TKA confer substantial improvement in patient outcome; however, greater joint specific, general health and satisfaction scores are reported following THA. This difference is physical in nature. Regression models are presented that can be applied to predict mean hip/knee arthroplasty outcome based on preoperative values.